The next viral pandemic-where do we stand - Fan, Rui; Liang, Qun; Sui, Yanbo; Yang, Yang; Yuan, Xingxing (Folia microbiologica, 2025)
The world is presently undergoing a recovery phase following the unexpected challenges posed by the coronavirus disease 2019 (COVID-19) pandemic. The loss of lives and the economic setbacks experienced by the global population will require considerable time to address. It is clear that future outbreaks, epidemics, or even pandemic caused by unknown bacterial, fungal, or viral pathogens are inevitable. In this context, public health front-liners will be essential in minimizing the impact of such incidents. This mini-review briefly discusses sociocultural issues, diagnostic capacities, surveillance, and screening strategies for potential future viral pandemic - referred to as Pandemic X. Additionally, it addresses treatment responses, vaccine development efforts, scientific advancements, policy considerations, and prospects for science communication related to forthcoming viral pandemics. While this review does not encompass all scientific approaches available on these topics, it aims to serve as a guideline for informing public health sectors about appropriate measures that should be undertaken.
Keywords: pandemie; Public Health; veřejné zdravotnictví; lidé; SARS-CoV-2; Pandemics; COVID-19; Humans